Eficiência das alocações nas funções orçamentárias de gestão ambiental dos municípios mais atingidos pela barragem de Brumadinho-MG - Marcus Vinícius Prates (2022)
The costs absorbed by public entities as a result of environmental disasters have increased, as well as the responsibilities for managing the resources applied to repair these events. The rupture of a tailings dam in Brumadinho/MG in 2019 gave the municipalities of the State of Minas Gerais the opportunity to manage values to be applied to the public service strengthening program. Given this context, the present study aimed to analyze the degree of efficiency of investments in budgetary functions of environmental management. With this, we sought to verify those municipalities that invested efficiently, as well as identify the inefficient ones and determine whether there was a displacement of this indicator over time in the municipalities affected by the Brumadinho-MG disaster. 26 municipalities located in the Paraopeba river basin were selected, namely those most affected by the dam failure. The time period between the years 2017 to 2021 was delimited. The efficiency of investments was valued having as inputs and outputs the environmental management and planning indices and the amount invested in the budgetary functions of urbanism, sanitation and environmental management, of which credits concerning the objectives of this study are allocated, all information extracted from SICOM – TCE\MG, relative to the municipalities in question. The Data Envelopment Analysis (DEA) tool was used, associated with the Malmquist Index. It justifies the research by the importance of valuing the efficiency of the resources invested for the economic and structural recovery of the municipalities and verifying relational and relevant aspects of the variables. Moreover, it is a resource linked to certain actions that refer to the strengthening of the public service. It was verified that the municipalities already presented, before the disaster event, a concept of low level of adequacy IEGM-TCE\MG. The calculation of the standard deviation showed that there were distortions in compliance with the requirements for completing the report between the units. However, there was a decrease in the amount of resources applied in budgetary functions associated with a reduction in the class of municipalities that had a low level of adequacy, denoting that these municipalities better applied public resources. In addition, for the years 2017 and 2018, it provided an increase in the efficiency of investments in environmental management functions and, in 2021, an increase in the number of municipalities that presented an indicator of technology change.